Case Report: Microglia Composition and Immune Response in an Immunocompetent Patient With an Intracranial Syphilitic Gumma - Yu, Qian; Li, Wei; Mo, Xiaohui; Tan, Fei; Yang, Lianjuan (Frontiers in Neurology, 2021)
The pathogenesis of intracranial syphilitic gummas remains poorly understood. Microglia are generally considered to be the main cell type of the innate immune system in the brain. Determination of the composition of infiltrating microglia of patients with typical intracranial syphilitic gummas may contribute to the understanding of the pathological process. We report a case of an intracranial syphilitic gumma who presented with right upper limb weakness. The histological analysis showed the presence of Treponema pallidum and infiltration with histiocytes. Immunostaining indicated that cells were predominantly the M2a and M2c, which were Arg-1+ and IL-10+. These findings suggest that there is an increased number of M2a/M2c microglia in intracranial syphilitic gummas, which may be part of the immune escape mechanisms triggered by Treponema pallidum.